(untitled) (Swiss Medical Weekly, 2010)
BACKGROUND/OBJECTIVE: In Switzerland, as in most developed countries, there has been a growing prevalence of excess weight in recent decades. However, within the country there may be regional variations. We investigated whether the trends in excess weight prevalence in the largest urban region differed from that in the rest of German Switzerland (GS). METHODS: We used individual data from four nationally representative Swiss Health Surveys (1992–2007) and from one survey conducted in the Canton of Zurich (ZH) in 2009. All studies used self-reported height and weight(18–74 years, N = 41 628). Prevalence rates of excess weight (BMI ≥ 25 kg/m2) were age standardised and population weighted. Odds ratios (OR: normal vs. excess weight) were obtained with weighted multivariable logistic regression. RESULTS: The prevalence of excess weight was lower in ZH than in GS, with increasing differences over time. In GS, OR increased in men (p trend 1992–2007 <0.001) and stagnated in women. In contrast, in ZH, OR stagnated in men and decreased in women (p trend 1997–2009 = 0.005). Within ZH, compared to the capital city, OR were higher in men in the less privileged part of the Metropolitan Area (p = 0.046) and in women not living in the Zurich Metropolitan Area (p = 0.049). CONCLUSION: In ZH, the prevalence of excess weight stagnated in men and decreased after having reached a peak in 1997 in women. This is the first study showing a decrease in Swiss adults, a population with internationally low excess weight prevalence. There is room for speculation whetherZH is a harbinger of the future situation in other regions of Switzerland and possibly other developed countries.